Latitudinal distribution of lanthanides contained in macroalgae in Chile: an inductively coupled plasma-mass spectrometric (ICP-MS) determination - Goecke, Franz; Aranguiz-Acuna, Adriana; Palacios, Mauricio; Munoz-Muga, Pilar; Rucki, Marian; Vitova, Milada (My University, 2017)
Lanthanide compositions of 17 Chilean macroalgal species were analyzed by inductively coupled plasma mass spectrometry. Samples were collected from four distinct areas (from 23A degrees to 53A degrees S) along the coast of Chile, in the spring of 2014. Lanthanides were confirmed in all samples and were found over a range of 0.0001-7.62 mg kg(-1) dry weight, in agreement with concentrations found in non-polluted areas around the world. The concentrations of elements varied among species, phyla, and, in some cases, by geographical distribution, highlighting the importance of local factors on lanthanide distribution. The central and northern zones of Chile contained higher concentrations of lanthanides (in total of all samples with 10.69 and 10.41 mg kg(-1) dry weight, respectively), although the northern samples comprised only one third of the number of samples from the central zone. The pristine area at the extreme south of Chile also contained lanthanides in macroalgal biomass, at a total concentration of 4.77 mg kg(-1) dry weight. Species with the highest concentrations of these metals were the brown alga Colpomenia sinuosa (7.62 mg kg(-1) dry weight) and the red macroalga Gracilaria chilensis (2.92 mg kg(-1) dry weight), followed by Corallina officinalis var. chilensis, and Pyropia sp. Cerium was normally the main lanthanide (2.99 mg kg(-1) dry weight) followed by lanthanum (1.34 mg kg(-1) dry weight) and/or neodymium (1.61 mg kg(-1) dry weight). This is the first publication that exclusively covers the distribution of these economically important metals in Chilean marine biota. We suggest that the brown alga C. sinuosa could have potential as a bioindicator of lanthanides.
Keywords: cerium; lanthanum; rare earth elements; seaweed; southamerica; trace elements